41.0k views
4 votes
Please help me! Its for my big test tomorrow!

Please help me! Its for my big test tomorrow!-example-1
User Ricky Mo
by
4.6k points

1 Answer

4 votes

QUESTION 11

Given :
\ln(3x-8)=\ln(x+6)

We take antilogarithm of both sides to get:


3x-8=x+6

Group similar terms to get:


3x-x=6+8

Simplify both sides to get:


2x=14

Divide both sides by 2 to obtain:


x=7

12. Given;
\log_3(9x-2)=\log_3(4x+3)

We take antilogarithm to obtain:


(9x-2)=(4x+3)

Group similar terms to get:


9x-4x=3+2


5x=5

We divide both sides by 5 to get:


x=1

13.
\log(4x+1)=\log25

We take antilogarithm to get:


(4x+1)=25

Group similar terms


4x=25-1


4x=24

Divide both sides by 4


x=6

14. Given ;
\log_6(5x+4)=2

We take antilogarithm to get:


(5x+4)=6^2

Simplify:


(5x+4)=36


5x=36-4


5x=32

Divide both sides by 5


x=(32)/(5)

Or


x=6(2)/(5)

15. Given:
\log(10x-7)=3

We rewrite in the exponential form to get:


(10x-7)=10^3


(10x-7)=1000


10x=1000+7


10x=1007

Divide both sides by 10


x=(1007)/(10)

16. Given:
\log_3(4x+2)=\log_3(6x)

We take antilogarithm to obtain:


(4x+2)=(6x)


2=6x-4x

Simplify


2=2x

Divide both sides by 2


1=x

17. Given
\log_2(3x+12)=4.

We rewrite in exponential form:


(3x+12)=2^4


(3x+12)=16


3x=16-12


3x=4

Divide both sides by 3


x=(4)/(3)

18. Given
\log_3(3x+7)=\log_3(10x)

We take antilogarithm to get:


(3x+7)=(10x)

Group similar terms:


7=10x-3x


7=7x

We divide both sides by 7


x=1

19. Given:
\log_2x+\log_2(x-3)=2

Apply the product rule to simplify the left hand side


\log_2x(x-3)=2

We take antilogarithm to obtain:


x(x-3)=2^2


x^2-3x=4


x^2-3x-4=0


(x-4)(x+1)=0

x=-1 or x=4

But x>0, therefore x=4

20. Given
\ln x+ \ln (x+4)=3

Apply product rule to the LHS


\ln x(x+4)=3

Rewrite in the exponential form to get:


x(x+4)=e^3


x^2+4x=e^3


x^2+4x-e^3=0

This implies that:


x=-6.91 or
x=2.91

User Orujimaru
by
5.0k points